What determines internationalization of emerging market firms? Experience from China - Li, MengYi (2009)
Emerging market firms and Chinese firms in particular are nowadays increasingly engaging in the extensive foreign investments in the global markets, thus this trend is noteworthy to study on. By investigating on the two cases of Chinese multinationals’ internationalization, the study here shows that the internationalization of Chinese firms is determined by entrepreneurship-based, patriotism-based, resource-based, market-based and institution-based factors. Therefore, an extended framework is presented to explain the determinants of Chinese firms’ internationalization, which is proposed to be also applied to other emerging markets enterprises.